FORMATION OF MORAL BEHAVIOR IN PRE-SCHOOL CHILDREN USING MULTIMEDIA (American Journal of Interdisciplinary Research and Development, 2026)
This article discusses the issues of forming moral behavior in preschool children with the help of multimedia technologies. The article discusses the role of modern information and communication tools, including multimedia programs, animations, videos and interactive games in the upbringing of children. The impact of these tools on the formation of positive qualities in children - respect, kindness, friendship, responsibility and moral standards is scientifically and pedagogically substantiated. The article shows the possibilities of developing children's interest, cognitive abilities and social behavior through the use of multimedia materials. It shows the importance of using multimedia technologies in the effective organization of moral education in preschool educational institutions.